2008
DOI: 10.1007/s00018-008-7456-0
|View full text |Cite
|
Sign up to set email alerts
|

The Sushi peptides: structural characterization and mode of action against Gram-negative bacteria

Abstract: The compositional difference in microbial and human cell membranes allows antimicrobial peptides to preferentially bind microbes. Peptides which specifically target lipopolysaccharide (LPS) and palmitoyl-oleoyl-phosphatidylglycerol (POPG) are efficient antibiotics. From the core LPS-binding region of Factor C, two 34-mer Sushi peptides, S1 and S3, were derived. S1 functions as a monomer, while S3 is active as a dimer. Both S1 and S3 display detergent-like properties in disrupting LPS aggregates, with specifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 144 publications
0
33
0
Order By: Relevance
“…This effect correlated with reduced binding of LPS to TP10-treated macrophages and was unrelated to its bactericidal activity. Endotoxin-neutralizing activity has been described for certain AMPs and peptides derived from diverse LPS-binding proteins (53)(54)(55)(56). Similar to TP10, the peptide antibiotic polymyxin B is able to inhibit the inflammatory action of LPS both in vitro and in vivo (57,58).…”
Section: Discussionmentioning
confidence: 99%
“…This effect correlated with reduced binding of LPS to TP10-treated macrophages and was unrelated to its bactericidal activity. Endotoxin-neutralizing activity has been described for certain AMPs and peptides derived from diverse LPS-binding proteins (53)(54)(55)(56). Similar to TP10, the peptide antibiotic polymyxin B is able to inhibit the inflammatory action of LPS both in vitro and in vivo (57,58).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we demonstrated that HMGB1 has two LPS-binding motifs located in its A and B box domains respectively, and that two synthetic peptides (HPep1 and HPep6) containing each of these LPS-binding motifs respectively, can inhibit LPS-stimulated TNF-α production both ex vivo in human PBMCs and in vivo in a mouse model of subclinical endotoxemia. Peptides derived from several LBPs, namely LBP, bactericidal/permeability-increasing protein, limulus anti-LPS factor [21], serum amyloid protein [22, 23], lactoferrin [24], cationic protein (CAP)18 [25], and CAP37 [26] antagonize LPS (review [27, 28]). To this list, we can now add the two novel HMGB1-derived peptides HPep1 and HPep6.…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of the extent of drug binding allowed us to determine the optimum drug loading required for achieving the highest antibacterial activity amongst all the NP-bioconjugates. Sushi peptides are biologically-active derivatives of the widely popular factor C protein found in horseshoe crabs 32 . Factor C proteins are extensively used in endotoxin detection assays such as the popular endotoxin test such as LAL tests 33, 34 .…”
Section: Discussionmentioning
confidence: 99%